Clinical Variability in P102L Gerstmann–Sträussler–Scheinker Syndrome. Issue 5 (4th September 2019) - Tesar, Adam; Matej, Radoslav; Kukal, Jaromir; Johanidesova, Silvie; Rektorova, Irena; Vyhnalek, Martin; Keller, Jiri; Eliasova, Ilona; Parobkova, Eva; Smetakova, Magdalena; Musova, Zuzana; Rusina, Robert
Abstract : Gerstmann–Sträussler–Scheinker syndrome (GSS) with the P102L mutation is a rare genetic prion disease caused by a pathogenic mutation at codon 102 in the prion protein gene. Cluster analysis encompassing data from 7 Czech patients and 87 published cases suggests the existence of 4 clinical phenotypes (typical GSS, GSS with areflexia and paresthesia, pure dementia GSS, and Creutzfeldt–Jakob disease–like GSS); GSS may be more common than previously estimated. In making a clinical diagnosis or progression estimates of GSS, magnetic resonance imaging and real‐time quaking‐induced conversion may be helpful, but the results should be evaluated with respect to the overall clinical context. ANN NEUROL 2019;86:643–652